TECHNOLOGY OF COOKING MEAT DISHES FROM «SOUS VIDE» PORK AND THEIR SENSORY ANALYSIS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The research paper analytically investigates and experimentally confirms the expediency of using “Sous Vide” method in the pork products cooking technology. On the base of analytical studies, it has been established that the culinary world is constantly evolving, new trends that challenge traditional methods and tastes of meat cooking appear. As consumers become more knowledgeable and demanding, take care of their health, chefs and food producers are exploring innovative methods and ingredients meet the demand for unique, environmentally friendly and nutritive options.The paper identifies the main advantages of cooking culinary products with “Sous Vide” method use, namely, improving the taste properties and preserving the rich aroma, reducing the weight loss of products during heat treatment, and significantly increasing the shelf life. The main quality indices of pork main dishes with “Sous Vide” method use, in particular, moisture mass fraction, moisture binding, moisture retention, fat retention ability and finished products output, were experimentally investigated.On the base of analytical and experimental studies and a number of technological developments, the technology for cooking pork main dishes with low-temperature processing use, namely by using “Sous Vide method”, was developed. It is provides increasing of the pork semi-finished products technological properties of and improving organoleptic and physical and chemical characteristics of the finished culinary meat products.In this research paper, the sensory analysis of culinary products from pork, namely chops and carbonade, produced by “Sous Vide” method, was carried out. It is established that the preparation of pork main dishes using the “Sous Vide” method use is more technologically advanced, efficient and provides finished products with increased nutritional and biological value.
Keywords: pork; meat products; "Sous Vide" method; low-temperature processing; semi-finished products; culinary products